STRATEGI PERENCANAAN PADA PELAYANAN JEMAAH UMRAH LANJUT USIA DI PPIU AMANA TOUR & TRAVEL PT. AMANA BERKAH MANDIRI UMBULHARJO YOGYAKARTA TAHUN 2020 - Fitria, Eni; Rosyid Ridla, Muhammad (UIN Sunan Kalijaga, 2022)
The increasing number of elderly people will affect various aspects of life related to the decline in physical, psychological and social conditions. This requires a planning strategy that must be carefully prepared, especially in the process of serving elderly Umrah pilgrims, so that elderly Umrah pilgrims get maximum service. As in the Indonesian Law No. 13 of 1998 concerning Elderly Welfare, one of which is social protection. This study aims to determine the planning strategy for the service of elderly Umrah pilgrims at PPIU Amana Tour & Travel PT Amana Berkah Mandiri Umbulharjo Yogyakarta in 2020. This research is a descriptive qualitative field research. Data collection uses observation, interview, and documentation methods. The data analysis method is data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the service of elderly Umrah pilgrims carried out by Amana Tour & Travel is quite good. Judging from the employees or mentors are responsible for the elderly Umrah pilgrims, have good knowledge and abilities, try to understand the needs of the congregation, and are able to provide trust. The planning strategies carried out by Amana Tour & Travel in the service of elderly Umrah pilgrims are optimizing facilities and infrastructure, maximizing the role of elderly Umrah pilgrims both in quality and quality.